Elemen Interior Berbahan Baku Pengolahan Sampah Styrofoam dan Sampah Kulit Jeruk - Michelli Wirahadi (Intra, 2017)
Styrofoam is another name of polystyrene which  has many advantages so often used in daily life. But styrofoam has a negative impact to health and environment because it can not decompose.  Besides styrofoam waste there many organic waste are not processed maximumly one of them is orange peel waste. Therefore, the authors have the idea of doing research which using the Styrofoam waste and orange peel waste in the process of making the interior elements. This research uses quantitative experimental method that required theorical testing involving casual relationship using numerical measures and analysis.The results of this research in the form of composition and steps of making interior element from styrofoam waste and orange peel waste processing along with product in form of partition panel.  The resulting product is 3 pieces of partition panel with size 0.8m x 1.8m. Other interior elements that are potentially generated include lights, coating materials and decorative elements.